Centrality of the childhood cancer experience and its relation to post‐traumatic stress and growth. Issue 4 (15th December 2020) - Cook, Jessica L.; Russell, Kathryn; Long, Alanna; Phipps, Sean
Abstract: Objective: Event centrality, the degree to which a traumatic event is perceived as central to one's identity, has been associated with post‐traumatic stress (PTS) symptoms and post‐traumatic growth (PTG) outcomes in various trauma samples. Trauma frameworks are widely used to understand the psychological impact of pediatric cancer; however, event centrality has not been studied in this population. We investigated event centrality in pediatric cancer survivors and healthy comparisons, and its relation with PTS and PTG outcomes. Method: Cancer survivors, age 13–23 ( N  = 196) and healthy comparisons ( N  = 131) completed the Centrality of Events Scale and PTS and PTG measures in reference to their most traumatic life event. Cancer survivors who first identified a non‐cancer‐related event repeated all measures in reference to cancer. Results: Centrality scores were significantly higher when referencing cancer compared to non‐cancer events, even in survivors for whom cancer was not rated as most stressful (53.1%). Centrality scores for non‐cancer events were not significantly different between survivors and healthy comparisons. Event centrality showed significant positive relations to both PTS and PTG outcomes. Conclusion: The pediatric cancer experience is perceived as central to survivors' identity regardless of whether the experience is perceived as highly traumatic. Centrality of cancer is a significant predictor of both positive and negative psychological outcomes in cancer survivors.